Unusual Presentation and Surgical Treatment of a Phosphaturic Mesenchymal Tumor in a Knee - Sun, Juan; Zhou, Xi; Xia, Weibo; Wu, Huanwen; Liu, Shuzhong; Wang, Huizhen; Liu, Yong (Frontiers in Surgery, 2022)
A 30-year-old woman presented to our hospital with an 11-year history of gradually enlarging masses around the left knee and 2-year history of progressively worsening bone pain. Tumor-induced osteomalacia (TIO), a rare paraneoplastic syndrome caused by phosphaturic mesenchymal tumors (PMTs) was suspected, but the postoperative pathology of her two operations was both reported as tenosynovial giant cell tumor (TGCT), making its diagnosis confusing. The possibility of hypophosphatemia, insufficient blood supply, innervation of the left lower limbs, as well as the unclear pathology, make it unreasonable to perform tumor-type knee prosthesis replacement directly. Finally, we placed static polymethylmethacrylate (PMMA) spacer at first, then when the concentration of blood phosphorus level rose to the normal range, the pathology was confirmed to be TIO, the blood supply and innervation was satisfying, tumor-type knee prosthesis replacement was performed. She was discharged post operative day 15 after the prothesis implantation without incident. One and a half years after her surgery, the concentration of blood phosphorus was still in the normal range, the symptom of systemic bone pain had improved significantly, the prosthesis was still in a good position and no recurrence was caught.